Sejarah, Prinsip, dan Perbedaan Antara Asuransi Takaful/Asuransi Syari’ah dan Asuransi Konvensional - Indra Hidayatullah (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2016)
The phenomenon of insurance actually arising from a group of people who are determined to establish a social gathering in order to alleviate the financial burden between them, as well as to avoid any financing difficulties they face.Currently the demand for insurance services is increasing perceived both by the households, businesses, and government. Such insurance is required as a means to face the risk of a more complex and varied. The danger that is feared that among others include: loss, damage, theft, fire, accident, illness, or even death.But a lot of variety and types of insurance that exist so that we sometimes confused and incorrect perception of where Islamic/Sharia and which are non-Islamic or even identical to the conventional? not least because of the type of insurance that is allegedly containing gharar/speculation, maisyir/chancy, usury, gambling and exploitation (often there is an imbalance between the value of the premiums and compensation), as well as their freedom of investment in the sectors of immoral and usury. Takaful insurance is insurance that are developed with a system of mutual risk sharing among members in a way each spend tabarru, namely outright funds paid for the purpose of bearing one another among members.